Nonlinear exposure-response associations of daytime, nighttime, and day-night compound heatwaves with mortality amid climate change - Jiangdong Liu; Ho Kim; Masahiro Hashizume; Whanhee Lee; Yasushi Honda; Satbyul Estella Kim; Cheng He; Haidong Kan; Renjie Chen (Nature Communications)
Abstract Heatwaves are commonly simplified as binary variables in epidemiological studies, limiting the understanding of heatwave-mortality associations. Here we conduct a multi-country study across 28 East Asian cities that employed the Cumulative Excess Heatwave Index (CEHWI), which represents excess heat accumulation during heatwaves, to explore the potentially nonlinear associations of daytime-only, nighttime-only, and day-night compound heatwaves with mortality from 1981 to 2010. Populations exhibited high adaptability to daytime-only and nighttime-only heatwaves, with non-accidental mortality risks increasing only at higher CEHWI levels (75th–90th percentiles). In contrast, compound heatwaves posed a super-linear increase in mortality risks after the 25th percentile of CEHWI. Associations of heatwaves with cardiovascular mortality mirrored those with non-accidental mortality but were more pronounced at higher CEHWI levels, while significant associations with respiratory mortality emerged at low-to-moderate CEHWI levels. These results highlight the necessity of considering the nonlinear health responses to heatwaves of different types in disease burden assessments and heatwave-health warning systems amid climate change.